Anti-mullerian hormone levels before and after ovarian drilling in polycystic ovary syndrome: has this an effect on fertility? - Mojgan Javedani Masroor; Hossein Sheybani; Shiva Sheybani; Nastaran Abolghasem (Reproductive Biology and Endocrinology, 2022)
Abstract Background Polycystic ovary syndrome (PCOS) is the most common endocrine, metabolic, and multi-causal disorder in the reproductive period with a possible genetic origin. Women with PCOS are characterized by oligo-ovulation, clinical or biochemical hyperandrogenism, and polycystic ovaries. Women with PCOS have an increased number of antral follicles. Anti-Mullerian hormone (AMH), a dimeric glycoprotein produced from the granulosa cells of the pre-antral and antral follicles, is elevated in PCOS. AMH has been implicated in two stages of follicle dysfunction that lead to the development of PCOS. The level of AMH decreases following ovarian drilling in patients with PCOS. The present study compared the level of AMH before and after Laparoscopic ovarian drilling (LOD) in patients with PCOS and its effect on fertility. Materials and methods This cohort study was carried out on 84 women with PCOS who underwent LOD in Akbarabadi Hospital in Tehran in 2020. Demographic characteristics, AMH, and estradiol levels were determined before surgery and compared with the amount one week after surgery. The effect of AMH level on pregnancy rate was also evaluated. Results The mean age of the patients was 29.01 ± 4.01 years. The mean Body Mass Index (BMI) of the patients was 26.33 ± 4.14 kg/m2. The results showed that the mean AMH level decreased significantly after ovarian drilling (P-value < 0.001). Menstrual cycle distribution was significantly different before and after LOD (P < 0.001). None of the variables had an effect on the pregnancy (P-value > 0.05). Oligomenorrhea in the previous menstrual period might cause AMH levels to increase by 3.826 units after LOD (P-value < 0.001). Conclusion Measuring serum AMH concentration before treatment can be a useful tool to predict LOD outcomes. This can help in selecting the patient for treatment. Trial registration The project was found to be under the ethical principles and the national norms and standards for conducting research in Iran with the approval ID and issue date of IR.IUMS.FMD.REC.1397.206 and 2018.08.26 respectively, which has been registered with the research project number 2766 in the Vice-Chancellor for Research and Technology Development of Iran University of Medical Sciences, School of Medicine, Tehran, Iran. URL: https://ethics.research.ac.ir/EthicsProposalView.php?id=34791 .